Ethnic influence of the lips and incisor in the diagnosis and orthodontic planning - Bagatini, Ana Thais [UNESP]; Tebaldi, Jaqueline Trento Negrão [UNESP]; Iplinsky, Nicole Tonin [UNESP]; Pinto, Suellen Tayenne Pedrosa [UNESP]; Santos-Pinto, Ary [UNESP] (FapUNIFESP (SciELO), 2024)
Introduction: Facial esthetics plays a fundamental role in the psychosocial development of human beings. Soft tissue analysis is an essential part of orthodontic diagnosis, treatment planning, and follow-up, with the lips, nose, and chin being important structures in facial composition. However, the position of the lips is of greater relevance, as it directly influences facial aesthetics, dental stability, and occlusion. Objective: To evaluate the relation of the lip projection with incisor inclination and skeletal facial pattern in a mixed Brazilian population. Material and method: Data derived from orthodontic records of 100 preadolescents 7 to 9 years of age and brown mixed ethnic origin. The sample was divided in two groups based on the photographic evaluation of the children´s facial profile considering the position of the upper and lower lips to the tegmental pogoniun and subnasal region by agreement of three evaluators. Group 1, normal protrusion of the upper and lower lips and Group 2, biprotrusion of the upper and lower lips. Lateral cephalograms were used to evaluate lip position, incisors inclination, facial growth pattern, and maxillomandibular anteroposterior relationship. Data analysis compared gender and group differences and the association between skeletal and dental variables with the labial position. Result: Protrusion of the upper and lower lips showed a weak but significant correlation with SNA angle and a moderate significant correlation with ANB angle. SNGoMe presented a weak, significant, and positive correlation with the lower lip protrusion to line B. IMPA and IS.SN showed a significant weak correlation with upper and lower lips protrusion for both B and S lines. Conclusion: There is no evidence of sexual difference in the skeletal, dental, or soft tissue relationship of Brazilian children 7 to 9 years of age of brown ethnicity. However, there is a significant correlation between lips protrusion and maxillary protrusion, maxillomandibular relationship, facial growth pattern, and inclination of the upper and lower incisors.
Influência étnica dos lábios e incisivos no diagnóstico e planejamento ortodôntico
Keywords: cephalometry; Lips; orthodontics